2004
DOI: 10.1002/nur.20053
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression and related psychosocial variables in Hong Kong Chinese women: Findings from a prospective study

Abstract: Research on predictors of postpartum depression (PPD) in Hong Kong (HK) Chinese women is scant. A prospective study with 385 HK Chinese postpartum women was conducted to identify correlations between PPD and demographic variables, and antenatal depression and psychosocial variables, and to determine which of these variables were predictors of PPD. Using the Edinburgh Postnatal Depression Scale (EPDS), we classified 19.8% of participants as postnatally depressed. Fifty-six percent of the variance in PPD was exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
2
14

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 34 publications
4
67
2
14
Order By: Relevance
“…Although the women appreciated the support received, especially with chores, meals, and infant care, the rituals were also found to be associated with stress, especially if the woman was confined to a small space and if they resided with their in-laws. Leung et al 27 also identified conflict between traditional and modern life as a stressor when investigating the experiences of mothers with PPD in Hong Kong. The depressed mothers reported enjoying some aspects of the postpartum rituals.…”
Section: Discussionmentioning
confidence: 99%
“…Although the women appreciated the support received, especially with chores, meals, and infant care, the rituals were also found to be associated with stress, especially if the woman was confined to a small space and if they resided with their in-laws. Leung et al 27 also identified conflict between traditional and modern life as a stressor when investigating the experiences of mothers with PPD in Hong Kong. The depressed mothers reported enjoying some aspects of the postpartum rituals.…”
Section: Discussionmentioning
confidence: 99%
“…Nove trabalhos analisaram relação entre DPP e suporte social em combinação com outros fatores (Dagher et al, 2011;Dennis & Letourneau, 2007;Dindar & Erdogan, 2007;Escribà-Agüir & Artazcoz, 2011;Fonseca et al, 2010;Kirpinar et al, 2010;Leung et al 2005;Özbaşaran et al, 2011;Xie et al, 2010), sendo que, em apenas um estudo (McVey & Tuohy, 2007), foi criado um índice geral de disponibilidade de apoio social, envolvendo oito fontes (parceiro, amigos, mãe, sogra, outras mulheres e homens da família, um visitador domiciliar e o médico). Os autores também usaram as mesmas fontes para criar um índice de satisfação com o apoio social, tendo encontrado que quanto menor a satisfação, maior o nível de sintomas depressivos.…”
Section: Relação Entre Depressão Pós-parto E Apoio Socialunclassified
“…Xie et al (2010) encontraram que, no período pré-natal, o baixo apoio do marido e dos pais e, no período pós-parto, o baixo apoio dos familiares, marido, pais e irmãs(ãos) estavam associados com aumento do risco de DPP. Finalmente, Leung et al (2005) (Sherbourne & Stewart, 1991), como é o caso de Fonseca et al (2010), avaliaram a frequência com que as mulheres julgavam receber, de fontes não especificadas, cinco tipos de apoio: emocional, afetivo, material, de informação e de interação social positiva.…”
Section: Relação Entre Depressão Pós-parto E Apoio Socialunclassified
“…Some authors advocate for research focused on the socially constructed, gendered values and norms that create or sustain postnatal depression (Edhborg, Friberg, Lyndh, & Widstrom, 2005;Leung, Martinson, & Arthur, 2005;Mauthner, 1999). Based on this approach, the postnatal period is similar to a period of metamorphosis for women.…”
Section: Introductionmentioning
confidence: 99%